Chemical constituents of Clerodendrum mandarinorum and their chemotaxonomic significance - Shi-Ya Tian; Feng Li; Huai-Qin Liu; Yu Qiu; Wu-Feng Li; Guang-Yan Liang; Chun-Chun Wang; Xue-Long Yan; Shang-Gao Liao; Qin-Feng Zhu (Biochemical Systematics and Ecology, 2026)

Correction: Ginkgo biloba extract as a retinal protective agent: a systematic review of preclinical experiments - Nannan Shi; Jiaxian Li; Yuefei Yan; Yu Jin; Weidao Zhang; Mengqiu Shang; Xiaoyu Wu; Yushi Cui; Lina Liang (Molecular Biology Reports, 2026)

Ginkgo biloba extract as a retinal protective agent: a systematic review of preclinical experiments - Nannan Shi; Jiaxian Li; Yuefei Yan; Yu Jin; Weidao Zhang; Mengqiu Shang; Xiaoyu Wu; Yushi Cui; Lina Liang (Molecular Biology Reports, 2026)

Origin of Early Cretaceous magmatism and its linkage with Cu–Fe–Au skarn mineralization in the Tonglushan ore field, eastern China: Evidence from whole-rock, zircon, and apatite geochemistry - Ming Zhang; Xiangzhou Li; Yanyan Zhao; Shichao Shang; Jiaming Zhou; Wan Huang; Yiheng Liu; Ziqing Yan; Xiaoyang Liu; Jun Tan (Lithos, 2026)

Calcium isotopes constrain magmatic–hydrothermal evolution and Nb–REE decoupling in the Bayan Obo carbonatite system - Zhuoming Li; Qingyan Tang; Chi Zhao; Hailong Jin; Shang Liu; Jiaolong Zhao; Biao Chen; Yanjiang Liu; Yan Zhang; Tianyu Qin; Min Qiao; Xinrui Bai; et al. (Gondwana Research, 2026)

Scalable MEA electrolyzers for ammonia electrosynthesis at ampere-level current densities - Xiaofang Zhang; Qingzhen Wang; Wen Gan; Kaiwen Yang; Zhijiao Ji; Yunpeng Xue; Shuangen Yu; Yunshan Shang; Junyu Yan; Xiaobo Cheng; Wenshi Li; Zhihua Han; et al. (Chemical Engineering Journal, 2026)

Microbial life history mediates the reduced temperature sensitivity of soil organic matter decomposition across an aridity gradient - Yan Yang; Liyang Yang; Wenhui Shang; Yan Du; Xiangzhen Li; Nianpeng He; Yakov Kuzyakov; Guirui Yu; Jing Tian (Soil Biology and Biochemistry, 2026)

Vortex dynamics and propulsive characteristics of three-dimensional rotating flapping foils: Effects of aspect ratio, spacing, and number of foils - Zhiyuan Shang; Zhanfeng Qi; Xuanyu Chen; Haolei Li; Yan Liu (Ocean Engineering, 2026)

A mineralizable and electroactive periosteum for promoting infected bone defect repair by remodeling the osteogenic microenvironment - Yangyang Qu; Linghanqing Wang; Xinyue Yang; Shixing Luo; Chongnan Yan; Nizhou Jiang; Yanchao Zhang; Jingyi Qu; Sida Chen; Yuanming Xiao; Yifeng Shang; Jun Li; et al. (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Characteristic flavors of different processed Yunnan specialty coffee after hot brewing: From sensory attributes to molecular recognition mechanism - Zelin Li; Ziqi Gao; Linyu Ni; Kaihua Lu; Dapeng Shang; Jingqiu Peng; Kunxian Wang; Jing Yan; Yifan Hu; Xiuwei Liu; Fangyu Fan; Hao Tian (Food Chemistry, 2026)

Feeding behavior rhythms of artificial Diet-Reared silkworms (Bombyx mori) based on Dual-Coordinate systems and multiscale signal analysis - Zhenghao Li; Yinfa Yan; Junjie Zhao; Mingrui Shang; Zhanhua Song; Jing Wang; Tingju Sun; Guizheng Zhang; Mochen Liu (Computers and Electronics in Agriculture, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Electrostatic-field-driven synergistic regulation of molecular conformation and mesostructure enables stable Na+ transport in 12 μm PVDF-HFP-based electrolytes - Jiaze Li; Rong Yang; Xiaobin Li; Aoyi Jiang; Xin Dong; Hongyu Shang; Yinglin Yan; Hyun Woo Kim; Jou-Hyeon Ahn (Chemical Engineering Journal, 2026)

A Statistical Quality-Control Framework for Sentinel-1 SAR Wind Speed Retrieval Based on First- and Second-Order Moments - Yan Wang; Xupu Geng; Yan Li; Xiaohui Li; Chenghan Luo; Shaoping Shang; Feng Zhang (Journal of Marine Science and Engineering, 2026)
Synthetic Aperture Radar (SAR) enables high-resolution sea-surface wind speed retrieval. However, the enhanced spatial resolution of SAR imagery introduces substantial challenges, from small-scale contamination sources that significantly degrade retrieval accuracy. Particularly in coastal regions, non-wind-related backscatter signals, such as ships and oil slicks, can severely bias wind speed estimates at sub-kilometer scales. In this study, the first-order moment (average, m1) and second-order moment (variance, m2) are computed from the normalized radar cross-section (NRCS) within sub-images of Sentinel-1 SAR data acquired in Interferometric Wide (IW) mode. Analysis reveals that clean-sea-surface signals in both VV and VH polarizations cluster around an approximately linear empirical trend, m2 = 2m1 + b, in the m1-m2 statistical feature space, whereas the examined contamination types deviate from this trend and occupy separable regions. Based on this characteristic, a quality-control framework is proposed for the systematic separation of clean sea surface from image noise (border noise and inter-swath stripe noise) and non-ocean targets (land contamination, bright targets, and dark spots). Validation using independent SAR data from the Taiwan Strait was conducted separately for native 10 m and height-adjusted 3 m buoy observations. For the native 10 m observations, the RMSE and MBE were essentially unchanged at 1.5 m/s and −0.3 m/s, respectively. For the height-adjusted nearshore observations, the RMSE decreased from 3.2 m/s to 2.1 m/s and the MBE changed from −1.5 m/s to −1.1 m/s.

Acute alcohol exposure induces reproductive behavior defects, subfertility, brain transcriptomic changes of parental zebrafish and malformation in their offspring - Li Peng; Jun-Yuan Lei; Yue-Ying Meng; Shang-Chun Li; Xiang-Yan Dai (Toxicology, 2026)

Garnet microtextures and geochemistry of the Tonglushan Cu–Fe–Au skarn deposit (Edong district): Constraints on fluid evolution and skarn mineralization - Ming Zhang; Xiangzhou Li; Ziqing Yan; Shichao Shang; Wan Huang; Yanyan Zhao; Jiaming Zhou; Xiaoyang Liu; Jingui Huang; Jun Tan (Journal of Geochemical Exploration, 2026)

Graphitic carbon nitride-loaded magnetic biochar mitigates the transmission of tetracycline and its resistance genes in a soil-lettuce continuum - Qing Wang; Tingli Luo; Haihua Zhang; Yaqi Cao; Yifan Dong; Shaojing Sun; Shang Ren; Xuli Li; Weimin Gu; Yan Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Comparison of soy protein isolate and soy protein concentrate in preparing high-moisture extruded meat analogues: Textural properties, physicochemical characteristics, and flavor profile - Xinyu Yan; Yang Gao; Mengyao Li; Jingwen Xu; Wanli Shang; Baokun Qi; Shizhang Yan; Lianzhou Jiang (Food Chemistry, 2026)

One-pot self-separating Janus hydrogel for wet tissue integration, hemostasis, anti-adhesion, and wearable biosensing - Wenhuan Huang; Yan Wang; Xiangcun Shang; Cong Li; Kaize Su; Dongli Li; Jingwei Jin; Panpan Wu; Keke Wu (Chemical Engineering Journal, 2026)

Study on the efficacy and fluoride removal mechanism of a novel silica-aluminum composite coagulant - Zisen Li; Ruoning Wu; Yong Shang; Weiyan Yin; Kangying Guo; Qinyan Yue; Yan Wang; Yue Gao; Baoyu Gao (Journal of Hazardous Materials, 2026)

Alkaline-induced surface reconstruction to Ni/NiO/Ni(OH)2 enables efficient hydrogen evolution - Jun Wu; Shuangyan Shang; Bowei Li; Lixin Zhang; Qunchao Zhang; Feng Wang; Chunsheng Li; Yan Sun; Huimin Wu (Fuel, 2026)

Design of novel bigel beads based on sodium alginate and monoglyceride for nutraceuticals delivery: Structural properties, gastrointestinal fate, and potential as dysphagia foods - Guangqian Hou; Ziyi Li; Youyi Yan; Shengqi Mei; Dan Chen; Longchen Shang; Shuai Chen (Food Research International, 2026)

Variations in semi- and non-volatile organic substances during physical recycling and their migration from rPET bottles - Yi-Qi Liu; Yan Zeng; Shao-Fu Zeng; Zhi-Wei Wang; Lei Zhu; Li-Li Jin; Gui-Qin Shang; Gui-Hua Liu; Chang-Ying Hu (Food Packaging and Shelf Life, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Effect of stiffness on the propulsive performance and vortex dynamics of a semi-active flapping foil near a free surface - Xuanyu Chen; Zhanfeng Qi; Zhiyuan Shang; Haolei Li; Yan Liu (Ocean Engineering, 2026)

Removal of Microcystis aeruginosa by Fe-doped biochar via persulfate activation: Catalytic performance and mechanistic exploration - Tiantian Li; Zhiwen Cheng; Lili Yan; Guofeng Shang; Zongdi Hao; Guoqing Shen; Pinhua Rao; Runkai Wang; Guanghui Li; Zhaoziyue Zhang; Benjiao Huo (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insight into the “intermediate effect”: Competitive adsorption and surface coverage model in controlling hydrate formation in a closed-cell foam–SDS system - Yi-Feng Wang; Zhen-Guo Qi; Zhen Pan; Li-Yan Shang; Zhi-Ming Liu; Jie Liu; Zhuo-Fan Ma; Long-Qi Meng (Chemical Engineering Journal, 2026)

Holocene flood clusters in East China driven by coupled ENSO-Western Pacific Warm Pool dynamics - Liang Zhou; Yan Su; Yufan Li; Shang Zheng; Hui Han; Peng Lu; Peipei Wang; Xuexiang Chen; Shi-Yong Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Selenium-enriched Lacticaseibacillus rhamnosus SHA113 alleviates fatigue under simulated high-altitude hypoxia in mice through intestinal microbiota and antioxidant modulation - Guanwen Liu; Yinghui Li; Chi Li; Mingliang Jin; Xiaoya Shang; Dongyan Shao; Chunmei Jiang; Lu Yan; Bin Jia; Dachuan Yin; Junling Shi (Food Bioscience, 2026)

Exposure to magnesium oxide nanoparticles induces mitochondrial dysfunction and apoptosis in fish Megalobrama amblycephala by disrupting magnesium homeostasis - Ling Zhang; Zi-Shang Liu; Si-Si Xiong; Yan-Zou Dong; Yue-Yun Guo; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu; Xiang-Fei Li (Aquatic Toxicology, 2026)

Atomic manufacturing enables order modulation in nanostructured alloys for ultrahigh strength–ductility synergy - Hang Zhao; Jing Zhou; Baoshuang Shang; Yuqiang Yan; Xing Tong; Xinxin Li; Haijie Xian; Yong Ding; Bo Zhang; Haibo Ke; Wei-Hua Wang (Science Bulletin, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Two CC motif chemokine 20-like genes differentially regulate leukocyte migration and survival via CC chemokine receptor 6 in ayu (Plecoglossus altivelis) - Jia-Feng Cao; Yan Zhou; Li-Jun Duan; Shi-Li Shang; Qian-Jin Zhou; Jiong Chen (Fish & Shellfish Immunology, 2026)

Slow-release fertilizers applied in conjunction with manure enhanced soil quality and rice grain yield by regulating labile nutrient pools, soil enzyme activities, and soil structure - Qing Shan Xu; Yu Lian Yan; Hang Feng Wang; Shang Pan Li; Chun Xin Chi; Ya Li Kong; Wen Hao Tian; Xiao Chuang Cao; Lian Feng Zhu; Qiao Ling Li; Jing Wang Li; Jun Hua Zhang; et al. (Field Crops Research, 2026)

Constructing multiphase Co–Ni–S nanostructures for enhanced bifunctional electrocatalysis in urea electrolysis - Fozia Sultana; Jiale Shang; Jie Zhang; Weilong Wang; Renkun Li; Kexin Sun; Xiaoqing Yan; Tongtong Li; Renhong Li (Chemical Engineering Journal, 2026)

Denitrification in Suspended Sediment Systems at Different Riparian Distances: Performance and Metabolism Analysis - Shang Shi; Songqi Liu; Dapeng Li; Xinrui Yan; Ziyu Li; Zikui He; Jun Hou; Yangyang Yang (Water, Air, & Soil Pollution, 2026)

The Role of Fibro/adipogenic Progenitors (FAPs) in Sarcopenia: Mechanisms and Potential Therapeutic Strategies - Peng Zhan; Sen-bo Yan; Yue Liu; Xue-xun Li; Jing Geng; Hai-tao Yuan; Guo-kai Shang (Stem Cell Reviews and Reports, 2026)

Comparative analysis of the structure and function of gut microbiota in wild versus captive whooper swans using 16S rRNA high-throughput sequencing - Yan Shao; Yunpeng Liu; Haiting Ding; Lei Li; Yufeng Zhao; Yanmei Wang; Jun Wang; Shuai Shang (Biologia, 2026)

Danhong Injection targets CaMKII through Dihydrotanshinone I to alleviate cardiomyocyte death and inflammation in viral myocarditis - Junxia Zhang; Chengcheng Zhao; Wenjia Zhang; Mao Zhang; Fan Li; Haibao Shang; Wen Zheng; Yingjia Li; Li Quan; Xiaochuan Li; Huihui Li; Luyun Wang; et al. (Science China Life Sciences, 2026)

Growth environment of the Pacific oyster (Crassostrea gigas) reefs recorded by shells and sediment since mid-Holocene on the coastal plain of the Western Bohai Sea, China - Yi-ming Huo; Yue Zhao; Chang-fu Fan; Yan-he Li; Bin Hu; Zhi-wen Shang; Fu Wang; Hong Wang (Geo-Marine Letters, 2026)

Numerical investigation on wave conversion performance of a wave-powered vertical profiler - Yan Liu; Haolei Li; Zhanfeng Qi; Xuanyu Chen; Zhiyuan Shang; Ziwen Xing; Liang Cheng (Ocean Engineering, 2026)

Recovering residual carbon from coal gasification slag via flotation for wastewater treatment - Haiyu Wang; Jufen Zhu; Qi Yan; Jiale Wen; Junfei Shang; Xiaoyong Fan; Baoning Li; Fanhui Guo; Qingbo Wei; Lingxing Zan; Yuxuan Liu; Jian Li; et al. (Journal of Water Process Engineering, 2026)

Overlooked role of quorum sensing and physiological response triggered by granular activated carbon in anaerobic wastewater treatment - Le Chen; Shuangshuang Li; Miao Yan; Jiasheng Zhang; Zezhou Shang; Wei Fang; Guangming Zhang; Panyue Zhang; Ying Li (Journal of Water Process Engineering, 2026)

YIP: optimized YOLOv11-seg for accurate intramuscular fat percentage prediction in pigs using non-invasive ultrasound imaging - Junhao Zhang; Hang Jiao; Genyuan Li; Hanhan Li; Chenglin Li; Pengsheng Dong; Yan Liu; Bo Jiang; Peng Shang; Feng Yang; Chunli Li; Xinjian Li; et al. (Science China Life Sciences, 2026)

Dynamic Strength Threshold-Based Prediction Model for Rock Mass Fragmentation Zoning in Blasting - Haiwang Ye; Menghao Yu; Yan Yu; Fengchuan Shang; Tao Lei; Ning Li; Qizhou Wang (Rock Mechanics and Rock Engineering, 2026)

Iron-nickel alloy co-reaction accelerator-based electrochemiluminescence platform with non-linear HCR-CHA cascade amplification for ultrasensitive quantitation of paraquat - Wen-Jie Zhong; Jia-Min Qin; Zhi Luo; Yun Li; Jia-Hui Zhou; Ruo Yuan; Wen-Bin Liang; Shang-Cheng Xu; Wei-Jing Yi; Yan Li (Analytica Chimica Acta, 2026)

Propulsion performance of a fully active hydrofoil: Effects of swing angle amplitude and asymmetry ratio - Xuanyu Chen; Yan Liu; Haolei Li; Zhiyuan Shang; Ziwen Xing; Zhanfeng Qi (Ocean Engineering, 2026)

Human umbilical cord MSC-derived exosomes attenuate radiation-induced pulmonary fibrosis via remodeling the gut-lung axis in mice - Yan Zhou; Haonan Wang; Ling Guo; Xiaodie Liu; Xing Wang; Yue Liu; Mengjuan Shang; Bo Zheng; Kewei Li; Lin Liu; Jing Li; Guirong Ding (Life Sciences in Space Research, 2026)

A novel method for remote sensing phycocyanin leveraging optical classification and an integrated machine learning algorithm - Shizhuo Liu; Chong Fang; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Sijia Li; Hui Tao; Zhaojiang Yan; Lili Lyu; Yunfeng Lyu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Rational design of zeolite-based composite catalysts in catalytic cracking of polyethylene - Yan Li; Zhe Ma; Jingyuan Shang; Ting Wang; Xingong Zhang; Peng Xu; Chenzhao Wang; Xiang Feng; De Chen; Chaohe Yang; Xiaobo Chen (Fuel, 2026)

Revealing the role of spin state in catalysis: Medium spin Fe3+ catalyst for lithium‑sulfur batteries - Xin Dong; Rong Yang; Xifei Li; Peiying Li; Yurou Wang; Xuchen Li; Hongyu Shang; Jiaze Li; Chaojiang Fan; Yinglin Yan; Yunhua Xu (Chemical Engineering Journal, 2026)

GLS1 inhibitor CB-839 inhibits the malignant progression of 5-FU resistant hepatoma cells by regulating glutamine metabolism - Hao Wang; Xiao-yan Wang; Jian-bo Ji; Zong-xue Zheng; Peng-fei Shang; Xiu-li Guo (Chemico-Biological Interactions, 2026)

APOE Lipoprotein Particles: Pathophysiology, Therapy, and the Crosstalk in Alzheimer’s Disease and Cardiovascular Disease - Chan Liu; Juan Liu; Yan-Yang Wang; Shang-Fu Xu; Li-Mei Yu (Molecular Neurobiology, 2026)

Synergy of nanoclusters/single atoms regulates sustainable oxidation pathways for self-motivated Fenton-like processes - Mengyao Fan; Yanwei Li; Tianran Zhang; Zhaokai Gao; Yan Wu; Yanan Shang; Zongchao Huo; Xuemin Zhao; Yue Gao; Longlong Geng; Xing Xu (Water Research, 2025)

Groundwater depletion in China’s Granary: The unintended consequences of cropping pattern shifts - Yiqun Shang; Jinwei Dong; Ping Fu; Nanshan You; Xi Zhang; Yuanyuan Di; Yan Zhou; Xi Chen; Zhichao Li; Xinqi Zheng (Journal of Hydrology, 2025)

Deep insights into LDH reconstruction for enhanced capacitive deionization - Xiaohong Shang; Jinguo Hu; Yaping Yan; Siyu Li; Jiameng Diao; Haoyu Wang; Bin Hu; Hao Wang (Journal of Environmental Chemical Engineering, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Carbon dot phosphorescent sonosensitizer sensitized copper-based phenolic nanosheets for cuproptosis/sonodynamic/chemodynamic synergistic tumor therapy co-amplified immunotherapy - Lang Yan; Yuanbo Shang; Nan Wang; Xiqian Cao; Lijun Ren; Xinyi Zhao; Linchang Li; Jingbo Chen; Bing Ma; Bijiang Geng (Chemical Engineering Journal, 2025)

Light-enhanced π-π stacking of alginate-based supra-amphiphiles for structured droplet's stability and foliar deposition - Chaonan Shang; Shujuan Yang; Furui He; Linwang Fan; Yan Zhou; Qile Chen; Mingnan Zhang; Gaobo Yu; Yuhong Feng; Jiacheng Li (Chemical Engineering Journal, 2025)

A Facile-Synthesized Dual-Network Multi-Ionic Integrated Explosive with Enhanced Detonation Performance and Promoted Aluminum Reactivity - Yun-Fan Yan; Yu Shang; Ming-Yu Guo; Shao-Li Chen; Meng Cui; Zhi-Hong Yu; Wei-Xiong Zhang; Xiao-Ming Chen (Chemical Engineering Journal, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

First report on trait segregation in F1 hybrids between the cultivated peanut (Arachis hypogaea L.) and the wild incompatible species A. glabrata Benth. - Wei Jie Qi; Hao Jie Sun; Jing Yu; Chun Jiao Jiang; Guang Di Yuan; Shang Xia Li; Chun Yan Xu; Chuan Tang Wang (Genetic Resources and Crop Evolution, 2025)

Oxidase-mimic Fe-co-Ce oxide embellished chitosan fiber for quantitative degradation of luminol and visual detection of m-aminophenol - Lei Hu; Junkai Hao; Ruhui Shang; Huitian Zhi; Xujie Wang; Yingchao Yang; Hanning Song; Chenxi Li; Juan Yu; Zhengquan Yan (Analytica Chimica Acta, 2025)

Artificial intelligence-enhanced bioavailability studies: Advancing the quality of food - Huiyuan Cheng; Li Liu; Hongyan Zhang; Yang Yu; Yu Bai; Shang Wang; Mingliu Yang; Wenxu Lu; Jie Cheng; Yan Jin (Trends in Food Science & Technology, 2025)

High cold storage density of TBAB+R141b binary hydrate under normal pressure: Nucleation and cycle formation characteristics - Chuanxiao Cheng; Yunpeng Shang; Yanqiu Xiao; Chenxiang Yan; Haoran Zhu; Hongjin He; Zhi Shang; Yifei Hou; Zihan Li; Jinhai Zhang; Qianhao Zhang; Fan Wang; et al. (Chemical Engineering Journal, 2025)

Earthworm-driven modulation of atrazine biodegradation pathways in biofilters - Xinyi Li; Jibin Wang; Xinhong Wang; Yang Ou; Huiping Liu; Liming Yan; Minglian Shang (Chemical Engineering Journal, 2025)

Isoliquiritigenin alleviates radiation-induced intestinal injury in lung cancer by inhibiting TNF-α/caspase3 signaling pathway - Ya-ping Chen; Liang-liang Shi; Yang-yang Li; Yi-Ming Zhang; Shang-zu Zhang; Hong-dou Hou; Yan Chen; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Whitening and antioxidant activities of Inonotus sanghuang Extract and development of primary whitening gel products - Liang Zhang; Hui-Lin Zhao; Shang-De Peng; Sempere Deguol Mawunya; Yao Zhang; Hai-Chen Li; Yu Luo; Yan Wen (Natural Product Research, 2025)

Keystone microbial taxa identified by deep learning reveal mechanisms of phosphorus stoichiometric homeostasis in submerged macrophytes under different hydrodynamic states - Shenyang Pan; Wenlong Zhang; Feng Yan; Yanan Ding; Ferdi L. Hellweger; Jiahui Shang; Yuting Yan; Feng Yu; Yi Li (Water Research, 2025)

Quantifying mutual transport contributions of ozone and its precursors among adjacent county-level cities during typical pollution episodes - Demian Lai; Yifei Chen; Yangjun Wang; Yan Zhang; Lin Xu; Zijia Ma; Burcak Kaynak; Shikang Tao; Yu Shang; Li Li (Urban Climate, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Hypoxia-preconditioned ADSC exosomes encapsulated in a multifunctional dual-network hydrogel promote the healing and functional regeneration of seawater-immersed wounds - Jie Li; Zishuo Wang; Wenjing Yang; Yongchao Zhou; Tao Fu; Yuhui Zhang; Xuzhou Duan; Dong Liu; Lingtong Kong; Yan Shang; Yuchen Zhang; Xuhui Wang; et al. (Chemical Engineering Journal, 2025)

Mass spectrometry-based lipidomics combined with flavoromics reveal the mechanism of characteristic flavor formation in Chelidonichthys kumu bone soup treated with different edible oils by frying - Zixi Li; Meng Dong; Libo Qi; Shan Shang; Yan Guo; Lei Qin; Baoshang Fu (Food Bioscience, 2025)

Promotion of Fungal Bioactivity by Extracellular Polymeric Substances Under Phosphorus Deficiency - Shang Pan; Yizhou Jiang; Shihui Yan; Meiyue Xu; Yuyang Cao; Haoyang Weng; Zhijun Wang; Yixiao Shi; Zhen Li (Environmental Microbiology, 2025)
Extracellular polymeric substances (EPS) can work as a highly efficient nutrient source for many microorganisms. This study investigated the influences of EPS on the bioactivities of a typical phosphate‐solubilising fungus, that is Aspergillus niger . The EPS were extracted from Rhodotorula mucilaginosa , with the addition of varying levels of inorganic phosphates. Under phosphorus (P) limitation, the cell wall thickness of A. niger increased from ~0.2 μm to ~0.4 μm. The addition of EPS relieved this phenomenon under the stress. In addition, it showed that EPS significantly promoted microbial growth with a four‐fold increase in microbial biomass. For the treatment with the addition of sole inorganic phosphate, A. niger primarily secreted oxalic acid for phosphate solubilisation. However, for the treatment with sole EPS, the secretion of oxalic acid was inhibited, while the activity of acid phosphatase was promoted. Moreover, the concentration of oxalic acid was significantly reduced from approximately 90 to 1 mg/L during the co‐existence of inorganic phosphate and EPS. Meanwhile, the activity of acid phosphatase was also enhanced. Therefore, A. niger can balance its strategy of P solubilisation, depending on the types of P sources. Furthermore, EPS was preferentially utilised over inorganic phosphate. Our findings highlight the potential of EPS for sustainable P supply.

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Assessing the contribution of VOCs to SOA formation and identifying their key species during ozone pollution episodes in a typical petrochemical city - Xiaoyu Yan; Fuhong Gao; Yuanyuan Ji; Cong An; Rui Gao; Yanqin Ren; Junling Li; Xiaoshuai Gao; Likun Xue; Fanyi Shang; Jidong Li; Hong Li (Environmental Pollution, 2025)

Seasonal and regional differences of heavy metals and nutrients from the five mariculture areas of large yellow croaker: Implications for environmental and fish quality - Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Jia-Lang Zheng; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Environmental Pollution, 2025)

In-situ regulation of Cu single-atom sites with axial nanoclusters in MOFs for selective Fenton-like reactions in water decontamination - Chao Yang; Shanshan Shang; Yixuan Wang; Pei Wang; Lianpeng Sun; Xiao-yan Li (Chemical Engineering Journal, 2025)

Ultra-stable all-solid-state lithium metal batteries facilitated by in-situ LiF-rich single-ion conductor composite polymer electrolytes - Jiaze Li; Rong Yang; Aoyi Jiang; Qianwei Zhang; Xin Dong; Hongyu Shang; Yinglin Yan; Yunhua Xu; Jou-Hyeon Ahn (Chemical Engineering Journal, 2025)

Enhancing ion shuttling through hydrogen bonding effect in ZnV2O4 aqueous zinc ion battery cathode - Lei Tan; Zhao Li; Lei Wang; Yu Shang; Zhiguo Wang; Zhengwang Tong; Yan Li; Xiangming Li (Chemical Engineering Journal, 2025)

A critical review on bioaugmentation assisted anaerobic digestion for methane production: Performances, microbiome-functionalities and challenges - Le Chen; Shuangshuang Li; Jiasheng Zhang; Feng Zhen; Zezhou Shang; Miao Yan; Yajie Zhang; Panyue Zhang; Yongming Sun; Ying Li (Journal of Environmental Management, 2025)

Seismic performance of fire-damaged RC columns strengthened with CFRP grid-reinforced ECC matrix - Xing-yan Shang; Xin Chen; Ling-zhi Li; Jiang-tao Yu; Zhong-guan Zhou (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Seasonal Changes of Brown Carbon in an Industrial City of Central China: Importance of Water-Insoluble BrC - Guangxuan Yan; Ziyi Wang; Mingyang Hou; Jieqi Wang; Sai Shang; Ziyang Shang; Jiayi Li; Hao Yu; Zhiguo Cao; Zirui Liu (Aerosol Science and Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Dynamic host–guest/π–π multiple bonds of alginate-based super-amphiphiles reinforced the mechanical stability and foliar deposition of jammed emulsion droplet - Shujuan Yang; Furui He; Keyang Mai; Yan Zhou; Chaonan Shang; Haifang Liu; Yuhong Feng; Gaobo Yu; Jiacheng Li (Chemical Engineering Journal, 2025)

Comparison of water quality, planktonic community, and volatile organic compounds in the seawater from five cage culture areas of large yellow croaker - Jia-Lang Zheng; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2025)

Response of acetochlor degradation and bacterial community in black soil to the application of vermicompost - Xia Hou; Xinhong Wang; Yang Ou; Liming Yan; Huiping Liu; Xinyi Li; Minglian Shang (Biology and Fertility of Soils, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Regulating the photoexcited carrier transfer efficiency over graphdiyne/Ag3PO4 S-Scheme heterojunction for photocatalytic hydrogen production - Jing Xu; Qian Li; Yan Shang; Xinjie Ning; Mingxia Zheng; Zhiliang Jin (Journal of Environmental Chemical Engineering, 2024)

Analysis, accumulation, transformation, and impact of metallic nanoparticles in plants - Wenhua Li; Yan Tan; Guanjia Shang; Liqun Chen; Zhibin Wu; Yiqing Lin; Lin Luo; Yuan Yang (Journal of Environmental Chemical Engineering, 2024)

Overexpression of ZlMYB1 and ZlMYB2 increases flavonoid contents and antioxidant capacity and enhances the inhibition of α-glucosidase and tyrosinase activity in rice seeds - Wanhong Li; Yali Li; Bintao Zhang; Qing Ma; Hehe Hu; Anming Ding; Lianguang Shang; Zhaohui Zong; Weicai Zhao; Hao Chen; Hongbo Zhang; Zhongfeng Zhang; et al. (Food Chemistry, 2024)

Phenolic compounds in dietary target the regulation of gut microbiota: Role in health and disease - Qinqiu Zhang; Yi Xu; Danka Bukvicki; Yue Peng; Fan Li; Qing Zhang; Jing Yan; Shang Lin; Shuxiang Liu; Wen Qin (Food Bioscience, 2024)

Temporal and tissue-specific regulation of energy metabolism in the swimming crab Portunus trituberculatus during nitrite stress and recovery - Yi Jiang; Xiaochen Liu; Huicong Han; Yan Shang; Jitao Li; Baoquan Gao; Yichao Ren; Xianliang Meng (Marine Pollution Bulletin, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Fabrication of Fe-Ti heteroatom-based metal-organic framework with vantage defects for high-efficient arsenic removal from water - Shanshan Shang; Xinyu Chen; Chao Yang; Ying Zhou; Kaimin Shih; Lin Lin; Xiao-yan Li (Chemical Engineering Journal, 2024)

Optimal feature selection and crop extraction using random forest based on GF-6 WFV data - Yanli Gao; Zhanqing Zhao; Guofei Shang; Yubo Liu; Shizhuo Liu; Haiming Yan; Yanhong Chen; Xia Zhang; Weiguo Li (International Journal of Remote Sensing, 2024)

Spatio-temporal variations in dew and its relevance to drought in the Beijing-Tianjin-Hebei region of China - Xiaonan Guo; Xiaoyu Liu; Guofei Shang; Dexin Zhou; Yan Jiang; Xia Zhang; Hongyu Li (International Journal of Remote Sensing, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Physiological and Transcriptomic Analyses Provide Insights into Nitrite Stress Responses of the Swimming Crab Portunus trituberculatus - Yi Jiang; Xiaochen Liu; Yan Shang; Jitao Li; Baoquan Gao; Yichao Ren; Xianliang Meng (Marine Biotechnology, 2024)

Bimetallic NiCo-MOF engineering on foam nickel for efficient oxygen evolution reaction in wide-pH-value water and seawater - Shuangyan Shang; Weichang Li; Suyi Liu; Lixin Zhang; Qinyu Tang; Yu Ding; Chunsheng Li; Yan Sun; Huimin Wu (Chemical Engineering Journal, 2024)

Electrospinning fabrication of hollow C@TiO2/Fe3C nanofibers composites for excellent wave absorption at a low filling content - Bai Jiang; Jianxun Shang; Faying Zhang; Na Li; Yan Wang; Zuming Hu; Junrong Yu (Chemical Engineering Journal, 2024)

Shrub expansion increases nitrification and denitrification in alpine meadow soils - Yu-Chen Zhang; Bin Jia; Jie Chen; Yan-Mei Liang; Li Jia; Zhen-Huan Guan; Min Wei; Zhanhuan Shang; Xiao Gang Li (Applied Soil Ecology, 2024)

Rapid and sensitive detection of SARS-CoV-2 based on a phage-displayed scFv antibody fusion with alkaline phosphatase and NanoLuc luciferase - Yuxue Yan; Guofu Shang; Jiling Xie; Yingying Li; Shaomei Chen; Yanqin Yu; Ping Yue; Xiaoyan Peng; Min Ai; Zuquan Hu (Analytica Chimica Acta, 2024)

Enhancing the thermal cyclic reliability of salt-based shape-stabilized phase change materials by in-situ SiO2–C interconnectivity in rice husk carbon - Ziyuan Li; Yangjun Wang; Huan Wang; Shuai Zhang; Zhen Shang; Limei Tian; Yuying Yan (Journal of Cleaner Production, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Cypate-sensitized upconversion nanoprobes for intracellular and in-vivo ATP ratiometric detection - Wusen Zhou; Jiacheng Gong; Shan Lu; Zhuo Li; Yan Long; Xingjun Li; Renfu Li; Xiaoying Shang; Yan Liu; Datao Tu; Zhuo Chen; Xueyuan Chen (Chemical Engineering Journal, 2024)

Efficient synthesis of L-malic acid by malic enzyme biocatalysis with CO2 fixation - Jianping Shi; Yan Fan; Xinshan Jiang; Xianglong Li; Shang Li; Yanbin Feng; Song Xue (Bioresource Technology, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Using ultrasonic-assisted sodium bicarbonate treatment to improve the gel and rheological properties of reduced-salt pork myofibrillar protein - Zhong-Wei Wu; Xue-Yan Shang; Qin Hou; Jing-Guo Xu; Zhuang-Li Kang; Han-Jun Ma (Meat Science, 2024)

Effects of High-Water Fluoride Exposure on IQ Levels in School-Age Children: A Cross-Sectional Study in Jiangsu, China - Yuting Xia; Yan Xu; Ming Shi; Song Liu; Suwan Liu; Hui Wang; Chaoyong Dai; Yunjie Ye; Mao Liu; Li Shang; Yang Wang; Peihua Wang (Exposure and Health, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Effect of zinc(II) and caustic content on the decomposition of sodium aluminate solutions and relevance to the Bayer process - Lei Xu; Wen-mi Chen; Yan-jun Zhang; Shang Fan; Jian-qing Pi; Ming-li Wang (Hydrometallurgy, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

A mapping method for emission inventory and its application in air quality modeling - Jin Fan; Mengying Shen; Tingyu Yan; Kaicheng Zhang; Tongge Zhang; Chen Gong; Xinyun Tian; Yanan Shang; Xianyu Yang; Ping Shao; Wei Tang; Maoshan Li; et al. (Atmospheric Pollution Research, 2024)

Time-varying modal identification of structures under seismic excitations using a novel time-frequency method - Tian-Li Huang; Yan-Nan Wang; Xu-Qiang Shang (Soil Dynamics and Earthquake Engineering, 2024)

Heterogeneous reactions significantly contribute to the atmospheric formation of nitrated aromatic compounds during the haze episode in urban Beijing - Zhen Cheng; Xinghua Qiu; Ailin Li; Qianqian Chai; Xiaodi Shi; Yanli Ge; Theodore K. Koenig; Yan Zheng; Shiyi Chen; Min Hu; Chunxiang Ye; Rico K.Y. Cheung; et al. (Science of The Total Environment, 2024)

A proteomic study on gastric impairment in rats caused by microcystin-LR - Shang-Chun Li; Li-Hong Gu; Yan-Fang Wang; Li-Mei Wang; Liang Chen; John P. Giesy; Xun Tuo; Wen-Li Xu; Qian-Hui Wu; Yi-Qing Liu; Ming-Huo Wu; Yang-Yang Diao; et al. (Science of The Total Environment, 2024)

Extracting visual navigation line between pineapple field rows based on an enhanced YOLOv5 - Tian-Hu Liu; Yan Zheng; Jia-Shang Lai; Yi-Feng Cheng; Si-Yuan Chen; Bao-Feng Mai; Ying Liu; Jia-Yi Li; Zhong Xue (Computers and Electronics in Agriculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Identification of inducible CYP3 and CYP4 genes associated with abamectin tolerance in the fat body and Malpighian tubules of Spodoptera litura - Lin Liang; Jianyi Li; Long Jin; Kunpeng Yan; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Surimi freshness monitoring of 4D printing material with anthocyanin - Jun-qi Zhan; Jing-jing Fu; Dan-li Jin; Yan-wei Yuan; Shi-ke Shen; Gao-shang Li; Yue-wen Chen (Journal of Food Engineering, 2023)

Nonthermal plasma-activated polyvalent cerium-manganese bimetallic (hydro)oxide-functionalized nanographene for the removal of thallium(I) contaminants and mechanism exploration - Dongping Song; Tao Huang; Yinglan Luo; Di Wu; Shouze Li; Yujie Yan; Chaojun Yang; Qi Fang; Yuxing Wang; Yuxuan Feng; Nan Shang; Ming Xia; et al. (Journal of Cleaner Production, 2023)

Water network integration for industrial park based on numerical indicators - Xiao-Yan Fan; Xiao-Jie Li; Ya-Xuan Zhu; Zhi-Yong Liu; Yuan Shang (Journal of Cleaner Production, 2023)

Efficient nitrogen removal and robustness enhancement of a two-stage partial nitrification-anammox (PN/A) process with low sludge concentration for mature landfill leachate - Ying Yan; Xiyao Li; Shang Ren; Qiong Zhang; Di Wu; Jiazhong Zhou; Yongzhen Peng (Bioresource Technology, 2023)

Packed OV-SnO2-Sb bead-electrodes for enhanced electrocatalytic oxidation of micropollutants in water - Chao Yang; Lin Lin; Shanshan Shang; Shengshou Ma; Feiyun Sun; Kaimin Shih; Xiao-yan Li (Water Research, 2023)

Near-infrared-triggered chirality-dependent photodynamic therapy based on hybrid upconversion nanoparticle hydrogels - Tianyong Guan; Yan Liu; Jiayao Li; Mingmao Chen; Xiaoying Shang; Ping Hu; Renfu Li; Hang Gao; Datao Tu; Wei Zheng; Xueyuan Chen (Chemical Engineering Journal, 2023)

Deep Eutectic Solvents Based on L-Arginine and 2-Hydroxypropyl-β-Cyclodextrin for Drug Carrier and Penetration Enhancement - Jianhua Lv; Pan Wu; Yaru Fang; Wenchang Zhang; Dongwen Liu; Mi Wu; Lei Shang; Huaiguo Li; Yan Zhao (AAPS PharmSciTech, 2023)

Variations of PM2.5-bound elements and their associated effects during long-distance transport of dust storms: Insights from multi-sites observations - Qingpeng Meng; Caiqing Yan; Ruiyu Li; Tianle Zhang; Mei Zheng; Yue Liu; Miao Zhang; Guixia Wang; Yuming Du; Chunlin Shang; Peng Fu (Science of The Total Environment, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Aerobic granulation in an oxidation ditch using the residual sludge after extracting slime-extracellular polymer substances - Yan-Ru Jia; Zheng-Hong Wen; Yi-Jiang Shang-Guan; Zhi-Hua Li (Journal of Water Process Engineering, 2023)

Design and Experiment of Double Scissor Sugarcane Field Transporter - Bing Xu; Li-Min Tao; Shang-Ping Li; Yu-Xiao Yan; Yuan-ling Chen (Sugar Tech, 2023)

Effects and mechanisms of tea on obesity - Xiao-Yu Xu; Cai-Ning Zhao; Bang-Yan Li; Guo-Yi Tang; Ao Shang; Ren-You Gan; Yi-Bin Feng; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

Facile synthesis of micro-eggette patterned nanofiltration membrane with enhanced anti-fouling and rejection performance - Wentao Shang; Wenjie Liu; Weiliang Wang; Noman Khalid Khanzada; Jiaxin Guo; Mu Li; Xiaoyan Li; Jia-Yong Lao; Shin Young Jeong; Chi Yan Tso; Feiyun Sun; Alicia Kyoungjin An (Desalination, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Phase-change material cooling blanket: A feasible cooling choice during transport after exercise-induced hyperthermia - Xin Wang; Xueyi Shang; Xin Li; Shuyuan Liu; Bin Lai; Lizhi Ma; Ying Sun; Lan Ma; Bo Ning; Yan Li; Qian Wang (Journal of Thermal Biology, 2023)

Impact of restoration measures on plant and soil characteristics in the degraded alpine grasslands of the Qinghai Tibetan Plateau: A meta-analysis - Wenlong Li; Xuejing Shang; Hepiao Yan; Jing Xu; Tiangang Liang; Huakun Zhou (Agriculture, Ecosystems & Environment, 2023)

Survival, Energy Status, and Cellular Stress Responses of the Juvenile Swimming Crab Portunus trituberculatus under Acute Nitrite Stress - Xiaochen Liu; Daixia Wang; Yan Shang; Xuee Yu; Baoquan Gao; Jianjian Lv; Jitao Li; Ping Liu; Jian Li; Xianliang Meng (Fishes, 2023)
Nitrite is a common pollutant encountered in aquaculture systems. During intensive hatchery, accumulation of nitrite can cause massive mortality of juvenile crustaceans. However, the nitrite toxicity and cellular stress responses in juvenile crustaceans is not clearly understood. Here, we investigate the survival, energy metabolism, and cellular stress responses in juvenile P. trituberculatus, an important aquaculture species in China, under acute nitrite stress. The results revealed nitrite resulted in a significant decrease in survival rate of juvenile swimming crab. After nitrite exposure, the activity of catabolic enzymes, such as HK, PK, CS, and CPT-1, were initially enhanced, and then they showed significant decrease at the late stage of exposure, accompanied by reduction in ATP and adenylate energy charge (AEC). The impaired energy homeostasis was possibly associated with disturbed AMPK signaling and enhanced anaerobic metabolism, which was indicated by the high levels of LDH activity and HIF-1α expression. Furthermore, we found that nitrite stress can depress antioxidant systems and unfold protein responses, causing oxidative damage and endoplasmic reticulum (ER) stress, and this, in turn, can trigger autophagy and apoptosis through both caspase-dependent and caspase-independent pathways. The results of the present study improve our understanding regarding adverse effects of nitrite on P. trituberculatus and provide valuable information for hatchery management.

Limited driving characteristics of combustion instability in a swirling flame: An experimental study - Yunpeng Liu; Jinghua Li; Yingwen Yan; Shoutang Shang (Fuel, 2023)

A framework for estimating all-weather fine resolution soil moisture from the integration of physics-based and machine learning-based algorithms - Pei Leng; Zhe Yang; Qiu-Yu Yan; Guo-Fei Shang; Xia Zhang; Xiao-Jing Han; Zhao-Liang Li (Computers and Electronics in Agriculture, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Identification of high-temperature resistance to stripe rust and molecular detection of Yr genes in Chinese core collections of common wheat - Yangshan Hu; Yue Zhang; Kexin Lu; Yuxiang Li; Benju Yan; Xianming Chen; Hongsheng Shang; Xiaoping Hu (Crop Protection, 2023)

Effect of snow cover on water and heat transfer in alpine meadows in the source region of Yellow River - Zhaoguo Li; Shaobo Zhang; Xianhong Meng; Shihua Lyu; Xianyu Yang; Yinhuan Ao; Di Ma; Lunyu Shang; Lele Shu; Yan Chang (Science of The Total Environment, 2023)

Impacts of dust events on chemical characterization and associated source contributions of atmospheric particulate matter in northern China - Ruiyu Li; Miao Zhang; Yuming Du; Guixia Wang; Chunlin Shang; Yao Liu; Min Zhang; Qingpeng Meng; Min Cui; Caiqing Yan (Environmental Pollution, 2023)

Gold nanoclusters-engineered dual-emitting nanofibrous film for fluorescent discrimination and visual sensing of explosives - Wenxing Gao; Qiang Li; Wencheng Zhong; Xiaomeng Zhou; Yibo Ge; Qi-Long Yan; Li Shang (Chemical Engineering Journal, 2023)

scVAEBGM: Clustering Analysis of Single-Cell ATAC-seq Data Using a Deep Generative Model - Hongyu Duan; Feng Li; Junliang Shang; Jinxing Liu; Yan Li; Xikui Liu (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Spatial spillover effect of green finance on economic development, environmental pollution, and clean energy production across China - Chenggang Li; Xiangbo Fan; Yongxiang Hu; Ying Yan; Guofei Shang; Yuzhu Chen (Environmental Science and Pollution Research, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Reduced Hypoxia Tolerance and Altered Gill Morphology at Elevated Temperatures May Limit the Survival of Tilapia (GIFT, Oreochromis niloticus) under Global Warming - Yan Zhou; Yanjie Zhang; Shang Wei; Wei Li; Wenhao Li; Zhichao Wu; Shouwen Jiang; Ying Lu; Qianghua Xu; Liangbiao Chen (Fishes, 2022)
Nile tilapia (Oreochromis niloticus) is one of the most important food fishes in global aquaculture. The optimal rearing temperature for Nile tilapia is 27–30 °C; however, in some Asian breeding areas, such as south China, water temperatures in summer frequently exceed 35 °C for several days. Potential effects of long-term exposure to high temperatures on the survival and metabolism of tilapia are unclear. In this study, genetically improved farmed tilapia, age six weeks, were exposed to water temperatures of 28, 32, and 36 °C for 15 weeks. Mean survival rates and tolerance to hypoxia were significantly reduced, and respiratory rates were increased in fish reared at 36 °C, compared to the 28 and 32 °C treatments (p

Stress conditions induced circRNAs profile of extracellular vesicles in brain microvascular endothelial cells - Xiao-Li Min; Hecun Zou; Jianghong Yan; Qiang Lyu; Xiang He; Fei-Fei Shang (Metabolic Brain Disease, 2022)

p-Nitrophenol contaminated soil remediation in a spray-type coaxial cylindrical dielectric barrier discharge plasma system - Nan Jiang; Ying Qu; Zheng Yu; Bangfa Peng; Jie Li; Kefeng Shang; Na Lu; Yan Wu (Environmental Science and Pollution Research, 2022)

Mass Transfer during Hematitization and Implications for Uranium Mineralization in the Zoujiashan Deposit, Xiangshan Volcanic Basin - Teng Deng; Guoxiang Chi; Xiongjie Zhang; Zenghua Li; Deru Xu; Shengmiao Li; Pengfei Du; Pei Shang; Shaohao Zou; Wanpeng Zhou; Ke Xu; Hai Yan; et al. (Journal of Earth Science, 2022)

Sweet tea ( Lithocarpus polystachyus rehd.) as a new natural source of bioactive dihydrochalcones with multiple health benefits - Ao Shang; Hong-Yan Liu; Min Luo; Yu Xia; Xiao Yang; Hang-Yu Li; Ding-Tao Wu; Quancai Sun; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Genomic Analysis of the Principal Members of Antioxidant Enzymes in Simulated Stresses Response and Postharvest Physiological Deterioration in Cassava - Sang Shang; Yuqi Tang; Jing Dai; Chunlai Wu; Yan Yan; Weiwei Tie; Meiying Li; Jinghao Yang; Jian Zeng; Mingjie Chen; Wei Hu (Tropical Plant Biology, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Homeobox Gene Six3 is Required for the Differentiation of D2-Type Medium Spiny Neurons - Xiaolei Song; Haotian Chen; Zicong Shang; Heng Du; Zhenmeiyu Li; Yan Wen; Guoping Liu; Dashi Qi; Yan You; Zhengang Yang; Zhuangzhi Zhang; Zhejun Xu (Neuroscience Bulletin, 2021)
Medium spiny neurons (MSNs) in the striatum, which can be divided into D1 and D2 MSNs, originate from the lateral ganglionic eminence (LGE). Previously, we reported that Six3 is a downstream target of Sp8/Sp9 in the transcriptional regulatory cascade of D2 MSN development and that conditionally knocking out Six3 leads to a severe loss of D2 MSNs. Here, we showed that Six3 mainly functions in D2 MSN precursor cells and gradually loses its function as D2 MSNs mature. Conditional deletion of Six3 had little effect on cell proliferation but blocked the differentiation of D2 MSN precursor cells. In addition, conditional overexpression of Six3 promoted the differentiation of precursor cells in the LGE. We measured an increase of apoptosis in the postnatal striatum of conditional Six3 -knockout mice. This suggests that, in the absence of Six3, abnormally differentiated D2 MSNs are eliminated by programmed cell death. These results further identify Six3 as an important regulatory element during D2 MSN differentiation.

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Preferential capture of phosphate by an Enteromorpha prolifera–based biopolymer encapsulating hydrous zirconium oxide nanoparticles - Qian-Qian Zhong; Li Shen; Ya-Qin Zhao; Yu-Cui Hao; Li-Cong Meng; Yan-Juan Liu; Xing Xu; Ya-Nan Shang; Bao-Yu Gao; Qin-Yan Yue (Environmental Science and Pollution Research, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Nitrogen form and ratio impact phenolic accumulation and relative gene expression in Cyclocarya paliurus - Jian Qin; Xiliang Yue; Yan Ling; Yongsheng Zhou; Na Li; Xulan Shang; Shengzuo Fang (Trees, 2021)

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Promoter engineering for high ectoine production in a lower saline medium by Halomonas hydrothermalis Y2 - Shannan Li; Yan Shang; Qi Zhao; Yuanxiang Liu; Xueqian Dong; Wenkai Wang; Chunyu Yang (Biotechnology Letters, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Biological characteristic and biocontrol mechanism of Trichoderma harzianum T-A66 against bitter gourd wilt caused by Fusarium oxysporum - Fuli Zhang; Chang Liu; Yunhua Wang; Kai Dou; Faju Chen; Li Pang; Xiangxiang Kong; Changrui Shang; Yan Li (Journal of Plant Pathology, 2020)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Drug Elimination Alteration in Acute Lymphoblastic Leukemia Mediated by Renal Transporters and Glomerular Filtration - Yue Zhou; Bin Du; Min Kan; Shang Chen; Bo-Hao Tang; Ai-Qing Nie; Pan-Pan Ye; Hai-Yan Shi; Guo-Xiang Hao; Xiu-Li Guo; Qiu-Ju Han; Yi Zheng; et al. (Pharmaceutical Research, 2020)

Experimental and finite element analysis of marble with double pre-existing flaws under loading-unloading conditions - Yan-qi Song; Xiang-shang Li; Tao Zhou; Ming Li (Arabian Journal of Geosciences, 2020)

Study on Pollution Characterization and Source Apportionment of Daytime and Nighttime PM2.5 Samples in an Urban Residential Community in Different Weather Conditions - Yan Zhao; Lihong Feng; Yuwen Wang; Bodong Shang; Jianping Li; Penghao Han (Bulletin of Environmental Contamination and Toxicology, 2020)

MiRNA-211 triggers an autophagy-dependent apoptosis in cervical cancer cells: regulation of Bcl-2 - Shang Liu; Hongyan Wang; Jing Mu; Hao Wang; Yan Peng; Qi Li; Dongwei Mao; Liyuan Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Characterization of two novel Alu element-mediated α-globin gene cluster deletions causing α0-thalassemia by targeted next-generation sequencing - Zhiming Li; Xuan Shang; Shiqiang Luo; Fei Zhu; Xiaofeng Wei; Wanjun Zhou; Yuhua Ye; Tizhen Yan; Ren Cai; Xiangmin Xu (Molecular Genetics and Genomics, 2020)

Genipin attenuates dextran sulfate sodium-induced colitis via suppressing inflammatory and oxidative responses - Zhiguo Li; Tianyi Ma; Wei Zhang; Yingjie Shang; Yongle Zhang; Yan Ma (Inflammopharmacology, 2020)

Bacillus licheniformis escapes from Myxococcus xanthus predation by deactivating myxovirescin A through enzymatic glucosylation - Chuandong Wang; Xinlin Liu; Peng Zhang; Yan Wang; Zhifeng Li; Xun Li; Renqing Wang; Zhaohui Shang; Jingen Yan; Haifeng He; Jing Wang; Wei Hu; et al. (Environmental Microbiology, 2019)
Summary Myxococcus xanthus kills susceptible bacteria using myxovirescin A (TA) during predation. However, whether prey cells in nature can escape M. xanthus by developing resistance to TA is unknown. We observed that many field‐isolated Bacillus licheniformis strains could survive encounters with M. xanthus , which was correlated to their TA resistance. A TA glycoside was identified in the broth of predation‐resistant B. licheniformis J32 co‐cultured with M. xanthus , and a glycosyltransferase gene ( yjiC ) was up‐regulated in J32 after the addition of TA. Hetero‐expressed YjiC‐modified TA to a TA glucoside (TA‐Gluc) by conjugating a glucose moiety to the C‐21 hydroxyl group, and the resulting compound was identical to the TA glycoside present in the co‐culture broth. TA‐Gluc exhibited diminished bactericidal activity due to its weaker binding with LspA, as suggested by in silico docking data. Heterologous expression of the yjiC gene conferred both TA and M. xanthus ‐predation resistance to the host Escherichia coli cells. Furthermore, under predatory pressure, B. licheniformis Y071 rapidly developed predation resistance by acquiring TA resistance through the overexpression of yjiC and lspA genes. These results suggest that M. xanthus predation resistance in B. licheniformis is due to the TA deactivation by glucosylation, which is induced in a predator‐mediated manner.

Pre-treatment of salicylic acid enhances resistance of soybean seedlings to Fusarium solani - George Bawa; Lingyang Feng; Li Yan; Yongli Du; Jing Shang; Xin Sun; Xiaochun Wang; Liang Yu; Chunyan Liu; Wenyu Yang; Junbo Du (Plant Molecular Biology, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Pathogenicity of an FAdV-4 isolate to chickens and its genomic analysis - Kai-kun Mo; Chen-fei Lyu; Shang-shang Cao; Xia Li; Gang Xing; Yan Yan; Xiao-juan Zheng; Min Liao; Ji-yong Zhou (Journal of Zhejiang University-SCIENCE B, 2019)

Digitizing and modeling of structural planes in fractured rock mass tunnel based on SfM - Shang-qu Sun; Li-ping Li; Cheng-shuai Qin; Hong-liang Liu; Yan-huan Zhang; Xing-zhi Ba (Arabian Journal of Geosciences, 2019)

Pollution Characterization and Source Apportionment of Day and Night PM2.5 Samples in Urban and Suburban Communities of Tianjin (China) - Yan Zhao; Lihong Feng; Bodong Shang; Jianping Li; Guang Lv; Yinghong Wu (Archives of Environmental Contamination and Toxicology, 2019)

Orange and red carotenoid proteins are involved in the adaptation of the terrestrial cyanobacterium Nostoc flagelliforme to desiccation - Yi-Wen Yang; Yan-Chao Yin; Zheng-Ke Li; Da Huang; Jin-Long Shang; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2019)

Influence of provenance and shade on biomass production and triterpenoid accumulation in Cyclocarya paliurus - Bo Deng; Shengzuo Fang; Xulan Shang; Xiangxiang Fu; Yan Li (Agroforestry Systems, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Synergistic degradation of trans-ferulic acid in aqueous solution by dielectric barrier discharge plasma combined with ozone - Jingyu Ren; Nan Jiang; Jie Li; Kefeng Shang; Na Lu; Yan Wu (Environmental Science and Pollution Research, 2018)

Characterization of a splice variant of soybean ERECTA devoid of an intracellular kinase domain in response to shade stress - Junbo Du; Yan Li; Xin Sun; Liang Yu; Hengke Jiang; Qiulin Cao; Jing Shang; Mengyuan Sun; Yi Liu; Kai Shu; Jiang Liu; Taiwen Yong; et al. (Journal of Genetics, 2018)

Rheological Behavior of Protein Hydrolysates from Papain-treated Male Gonad of Scallop ( Patinopecten yessoensis ) - Jia-Run Han; Jia-Nan Yan; Yi Li; Jun Zhao; Yue Tang; Wen-Gang Jin; Wen-Hui Shang; Meng Zhang; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Ectopic expression of UGT84A2 delayed flowering by indole-3-butyric acid-mediated transcriptional repression of ARF6 and ARF8 genes in Arabidopsis - Gui-Zhi Zhang; Shang-Hui Jin; Pan Li; Xiao-Yi Jiang; Yan-Jie Li; Bing-Kai Hou (Plant Cell Reports, 2017)

Ribavirin attenuates the respiratory immune responses to influenza viral infection in mice - Shang-hui Liao; Yun Li; Yan-ni Lai; Ni Liu; Feng-xue Zhang; Pei-ping Xu (Archives of Virology, 2017)

Flavonol glycosides from the leaves of Elaeagnus pungens - Ying-ying Shang; Qin Qin; Meng-Shun Li; Hai-yan Xu; Yue-bin Ge (Natural Product Research, 2017)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

Post Plasma-Catalysis of Low Concentration VOC Over Alumina-Supported Silver Catalysts in a Surface/Packed-Bed Hybrid Discharge Reactor - Nan Jiang; Cheng Qiu; Lianjie Guo; Kefeng Shang; Na Lu; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2017)

Lipid Nanoparticles Loaded with an Antisense Oligonucleotide Gapmer Against Bcl-2 for Treatment of Lung Cancer - Xinwei Cheng; Qibing Liu; Hong Li; Chen Kang; Yang Liu; Tianqi Guo; Ke Shang; Chengyun Yan; Guang Cheng; Robert J. Lee (Pharmaceutical Research, 2017)

Effects of excessive equatorial cold tongue bias on the projections of tropical Pacific climate change. Part I: the warming pattern in CMIP5 multi-model ensemble - Gen Li; Shang-Ping Xie; Yan Du; Yiyong Luo (Climate Dynamics, 2016)

Ectopic expression of UGT75D1, a glycosyltransferase preferring indole-3-butyric acid, modulates cotyledon development and stress tolerance in seed germination of Arabidopsis thaliana - Gui-Zhi Zhang; Shang-Hui Jin; Xiao-Yi Jiang; Rui-Rui Dong; Pan Li; Yan-Jie Li; Bing-Kai Hou (Plant Molecular Biology, 2016)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Endogenous salicylic acid accumulation is required for chilling tolerance in cucumber (Cucumis sativus L.) seedlings - Chun-Juan Dong; Liang Li; Qing-Mao Shang; Xin-Yan Liu; Zhi-Gang Zhang (Planta, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Syntheses and antibacterial activity of Schiff bases from 16-isopropyl-5, 9-dimethyltetracyclo [10.2.2.0 1, 10 .0 4, 9 ] hexadec-15-ene-5, 14-dicarboxylic acid - Jian Li; Jie Song; Shi-Bin Shang; Xiao-Ping Rao; Yan-Qing Gao (Natural Product Research, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

High prevalence of Eimeria infection in dairy goats in Shaanxi province, northwestern China - Guang Hui Zhao; Li-Hui Lei; Chuan-Chuan Shang; Man Gao; Yan Qing Zhao; Chao-Xi Chen; De-Kun Chen (Tropical Animal Health and Production, 2012)

Polymorphisms in MC4R gene and correlations with economic traits in cattle - Meng Huang; Xue Gao; Jun Ya Li; Hong Yan Ren; Jin Bao Chen; Shang Zhong Xu (Molecular Biology Reports, 2010)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

Crystallisation conditions (T, P, fO2) from mineral chemistry of Cu- and Au-mineralised alkaline intrusions in the Red River–Jinshajiang alkaline igneous belt, western Yunnan Province, China - Bi Xianwu; Hu Ruizhong; J. J. Hanley; J. E. Mungall; Peng Jiantang; Shang Linbo; Wu Kaixing; Suang Yan; Li Hongli; Hu Xiaoyan (Mineralogy and Petrology, 2009)

Association analysis of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Qian-Fu Gan; Lu-Pei Zhang; Jun-Ya Li; Guan-Yu Hou; Heng-De Li; Xue Gao; Hong-Yan Ren; Jin-Bao Chen; Shang-Zhong Xu (Journal of Applied Genetics, 2008)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)